Community policing, police militarization, and Canada’s colonial project - Samuels-Wortley, Kanika (Police and state crime in the Americas, 2024)
Canada’s global reputation as a haven for racial minorities has allowed the country to escape mainstream explorations into how the country’s national police force, a state-sanctioned institution, was created to uphold colonialist policies to ensure compliance within Indigenous and racial minority communities. Thus, at its core, policing models in Canada have played a direct role in the historical exploitation and marginalization of Indigenous and Black bodies. Modern police services often focus on building public trust. However, increased militarization counters these efforts and reinforces state power through violence and increased surveillance of racialized communities. Therefore, modern policing continues to promote the status quo, maintaining current power structures. Through the lens of procedural justice, the chapter examines the negative impact increased militarization has on police legitimacy within racial minority communities in Canada.